Ectopic fat deposition contributes to age-associated pathology in Caenorhabditis elegans - Palikaras, K.; Mari, M.; Petanidou, B.; Pasparaki, A.; Filippidis, G.; Tavernarakis, N. (J Lipid Res, 2017)
Age-dependent collapse of lipid homeostasis results in spillover of lipids and excessive fat deposition in nonadipose tissues. Ectopic fat contributes to lipotoxicity and has been implicated in the development of a metabolic syndrome that increases risk of age-associated diseases. However, the molecular mechanisms coupling ectopic fat accumulation with aging remain obscure. Here, we use nonlinear imaging modalities to visualize and quantify age-dependent ectopic lipid accumulation in Caenorhabditis elegans We find that aging is accompanied by pronounced deposition of lipids in nonadipose tissues, including the nervous system. Importantly, interventions that promote longevity such as low insulin signaling, germ-line loss, and dietary restriction, which effectively delay aging in evolutionary divergent organisms, diminish the rate of ectopic fat accumulation and the size of lipid droplets. Suppression of lipotoxic accumulation of fat in heterologous tissues is dependent on helix-loop-helix (HLH)-30/transcription factor EB (TFEB) and autophagy. Our findings in their totality highlight the pivotal role of HLH-30/TFEB and autophagic processes in the maintenance of lipid homeostasis during aging, in addition to establishing nonlinear imaging as a powerful tool for monitoring ectopic lipid droplet deposition in vivo.
Keywords: *Aging; *imaging; *lipotoxicity; *nonlinear phenomena; *second harmonic generation; *third harmonic generation; Adipose Tissue/*metabolism/pathology; Aging/genetics/*metabolism; Animals; Autophagy/genetics; Basic Helix-Loop-Helix Leucine Zipper Transcription Factors/*genetics/metabolism; Caenorhabditis elegans/genetics/metabolism; homeostasis; Humans; Lipid Metabolism/*genetics; Longevity/genetics/physiology; signal transduction